2018
DOI: 10.1016/j.ydbio.2018.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Coupling the roles of Hox genes to regulatory networks patterning cranial neural crest

Abstract: The neural crest is a transient population of cells that forms within the developing central nervous system and migrates away to generate a wide range of derivatives throughout the body during vertebrate embryogenesis. These cells are of evolutionary and clinical interest, constituting a key defining trait in the evolution of vertebrates and alterations in their development are implicated in a high proportion of birth defects and craniofacial abnormalities. In the hindbrain and the adjacent cranial neural cres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 118 publications
2
51
0
1
Order By: Relevance
“…However, it remains challenging to envisage how factors such as PBX proteins with widespread presence can confer functional specificity to HOX proteins, which exhibit domain-restricted localization in vivo. Of note, recent studies have demonstrated that HOX proteins do in fact bind specific sequences in vivo and drive the expression of different target genes at different times in different tissues, thus executing distinct developmental programs (Alexander et al 2009;Crocker et al 2015;Beccari et al 2016;Sheth et al 2016;Jerkovic et al 2017;Parker et al 2018).…”
Section: Partnerships Of Pbc Tfsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it remains challenging to envisage how factors such as PBX proteins with widespread presence can confer functional specificity to HOX proteins, which exhibit domain-restricted localization in vivo. Of note, recent studies have demonstrated that HOX proteins do in fact bind specific sequences in vivo and drive the expression of different target genes at different times in different tissues, thus executing distinct developmental programs (Alexander et al 2009;Crocker et al 2015;Beccari et al 2016;Sheth et al 2016;Jerkovic et al 2017;Parker et al 2018).…”
Section: Partnerships Of Pbc Tfsmentioning
confidence: 99%
“…In the vertebrate embryo, the HB is transiently subdivided into distinct units called rhombomeres (Rs) and lateral outpocketings that form the brachial arches (BAs), which are populated by migrating neural crest cells (NCCs) ( Fig. 1; Parker et al 2018). Unique combinations of HOX proteins confer segmental identity along the HB (Fig.…”
Section: Pbx Homeoproteins Drive Activation Of the Hox Gene Cascade Imentioning
confidence: 99%
“…Homeobox or HOX genes encode conserved transcription factors that regulate anterior‐posterior (A‐P) developing pattern and have been elaborated in detail over the last decade for their roles in the mechanisms underlying embryonic development . Recently, increasing evidence indicates that dysregulation of HOX family members maybe appear critical for the promotion of carcinogenesis .…”
Section: Introductionmentioning
confidence: 99%
“…Homeobox or HOX genes encode conserved transcription factors that regulate anterior-posterior (A-P) developing pattern and have been elaborated in detail over the last decade for their roles in the mechanisms underlying embryonic development. 3 Recently, increasing evidence indicates that dysregulation of HOX family members maybe appear critical for the promotion of carcinogenesis. [4][5][6] Preciously, we performed cDNA microarray and validated several differentially expressed HOX genes in GC-especially HOXA1, HOXA10, and HOXA13-with significantly higher expression in the cancerous tissues.…”
Section: Introductionmentioning
confidence: 99%
“…PA2 is homologous to the hyoid arch of gnathostomes, forming the velar support cartilage, while PA3-8 hold gills, like the posterior pharyngeal arches in aquatic gnathostomes. In gnathostomes, Hox PG2-4 genes have nested expression in pharyngeal arch NC that is broadly conserved between species, but paralogues often exhibit differences in expression levels (Parker et al, 2018). Previous studies in lamprey found conservation of select Hox domains in NC populations between lamprey and gnathostomes (Takio et al, 2007; Takio et al, 2004).…”
Section: Discussionmentioning
confidence: 99%